Analisis Pengelolaan Dan Pemanfaatan Dana Pensiun Oleh Nasabah PT TASPEN (Persero) Kcu Medan - Dwi Indah Pertiwi; Marliyah Marliyah (Lembaga Pengembangan Kinerja Dosen, 2023)
In principle, pension funds replace employee benefits. Taspen is a pension and insurance program organizer that serves ASN, judges, and civil servants. The source of funding for this pension program comes from the basic salary (gapok), additional basic salary, as well as the last monthly additional basic salary. So in essence, civil servants who have retired can rely on Taspen to manage their pension funds, which will be given in the form of monthly payments in accordance with applicable regulations. So here researchers carry out an analysis to find out what the customers in question are using the pension funds for. Are these funds managed and utilized well? This research uses a qualitative approach. data was collected using the interview method. After all the data has been collected, data analysis is carried out. The data analysis used is non-statistical data analysis. In this research, what is analyzed is the data collected in interview transcripts. Based on the research results, it is known that customers can use pension funds for various purposes, such as living costs. when retiring, investing, purchasing property, or supporting the education of children or grandchildren. Apart from that, customers also manage pension funds by carrying out financial planning, selecting investment portfolios, carrying out evaluations and monitoring, making wise expenditures, carrying out and considering insurance and protection, then consulting with financial experts.